Sodium Valproate versus Amitriptyline in the Prophylactic Treatment of Migraine - Dastegir Khan, Shahjada Mohammad; Walida, Salma Akhtar; Mohammed Shoab, Abul Kalam; Momen Khan, Muhammad Abdul; Hossain, Sakhawat; Wadud, Md Shaheen; Hossain, Khan Md Muzammel (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Drug prophylaxis of migraine is a safe and effective way of reducing the attack of headache frequency and the economic burden of migraine. Several drugs have been shown to be efficacious in double-blind placebo-controlled trials. Many patients avoid the regular intake of prophylactic drugs because of fear about the side effects, tolerance and addiction. Another reason for the low acceptance of migraine prophylaxis is that the efficacy of most drugs is limited and the burden of treatment cost. In this study two effective drugs, Amitriptyline and Sodium valproate are evaluated regarding their safety and efficacy. This study shows the comparative effectiveness, safety of both drugs and withdraw all the misconception about the prophylactic treatment of migraine among the patients and improve their life style adjustment and reduce the economic burden of the society. Objective: The purpose of the present study was to observe and compare the efficacy of Sodium Valproate and Amitriptyline in the prophylactic management of migraine patients. Methodology: This experimental study was carried out in the Department of Neurology at Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh during the period from January 2013 to December 2013. A total of 120 patients with migraine were selected of which 60 were treated with Amitriptyline (Group-A) and another 60 were treated with Sodium Volproate (Group-B). Both groups were observed for 6 months and the improvement of headache regarding frequency, severity and duration of episodes of headache was recorded in every 2 months follow up. Adverse effect of the drugs also monitored in both group. Result: Out of 120 patients the mean age was 32±8.64years and 34.23±8.09 in group-A and group-B respectively (p=0.147). There were 23 (38.3%) male and 37 (61.7%) female in group-A; whereas 17 (28.3%) male and 43 (71.7%) female in group-B (p=0.245). Thus the study was an age and sex matched study. It was observed that one third 20(33.3%) patients were house wife’s in group-A and 24(40.0%) in group-B. The difference was not statistically significant (p>0.05) between two groups. Frequency of attack per month before treatment was 6.25±5.21 in group-A and 7.80±4.1 in group-B. Frequency of attack per month after 2 months treatment was 4.30±4.14 and 6.19±4.10 in group-A and group-B respectively. Frequency of attack per month after 4 months treatment was 3.78±2.53 in group-A and 4.89±2.83 in group-B. Frequency of attack per month after 6 months treatment was 1.70±1.42 in group-A and 3.1±1.98 in group-B. Frequency of attack per month after 2, 4 and 6 months treatment was statistically significant (p<0.05) between two groups. It was observed that majority (88.3%) patients were improved headache in group-A and 23(38.3%) in group-B. The difference was statistically significant (p<0.05) between two groups. Conclusion: The pain intensity score is significantly decline in patients who received amitriptyline after treatment and almost similar in patients who received sodium valproate. Improved headache most of the patients who received Amitriptyline and less adverse effects developed in this group. Amitriptyline is more effective, seems to be safer than Sodium Valproate. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 126-131